Adsorption of reovirus to clay minerals: effects of cation-exchange capacity, cation saturation, and surface area. - Lipson, S M (1983)
The adsorption of reovirus to clay minerals has been reported by several investigators, but the mechanisms defining this association have been studied only minimally. The purpose of this investigation was to elucidate the mechanisms involved with this interaction. More reovirus type 3 was adsorbed, in both distilled and synthetic estuarine water, by low concentrations of montmorillonite than by comparable concentrations of kaolinite containing a mixed complement of cations on the exchange complex. Adsorption to the clays was essentially immediate and was correlated with the cation-exchange capacity of the clays, indicating that adsorption was primarily to negatively charged sites on the clays. Adsorption was greater with low concentrations of clays in estuarine water than in distilled water, as the higher ionic strength of the estuarine water reduced the electrokinetic potential of both clay and virus particles. The addition of cations (as chloride salts) to distilled water enhanced adsorption, with divalent cations being more effective than monovalent cations and 10(-2) M resulting in more adsorption than 10(-3) M. Potassium ions suppressed reovirus adsorption to montmorillonite, probably by collapsing the clay lattices and preventing the expression of the interlayer-derived cation-exchange capacity. More virus was adsorbed by montmorillonite made homoionic to various mono-, di-, and trivalent cations (except by montmorillonite homoionic to potassium) than by comparable concentrations of kaolinite homoionic to the same cations. The sequence of the amount of adsorption to homoionic montmorillonite was Al greater than Ca greater than Mg greater than Na greater than K; the sequence of adsorption to kaolinite was Na greater than Al greater than Ca greater than Mg greater than K. The constant partition-type adsorption isotherms obtained when the clay concentration was maintained constant and the virus concentration was varied indicated that a fixed proportion of the added virus population was adsorbed, regardless of the concentration of infectious particles. A heterogeneity within the reovirus population was indicated.